Use of FACS to determine cell death process in Chlamydia trachomatis Infected cells - Millán Mendoza, Beatriz; Eley, Adrián (Ciencia, 1970)
Cytotoxicity due to infection of obligate intracellular pathogen Chlamydia trachomatis, has been reported for many years, but the mechanisms involved in the cell death process remain controversial. C. trachomatis is responsible for several important ocular and genital tract infections worldwide and few techniques have been used to assess the cell death process of the mammalian host cells. In this report, simultaneous cell staining with Annexin V-FITC, a phospholipid binding protein, and the non-vital dye propidium iodide (PI), followed by fluorescence-activated cell sorting (FACS) analysis were used to characterize the cell death process in infected HeLa cells. Apoptosis found not to be activated in the infected cells until some point between 24 and 48 h in a dose-dependant relation; after 48 h, necrosis took over the cell death process. Thus, we demonstrate that the use of annexin V-FITC/PI staining followed by FACS analysis offers an alternative for assessing the cell death process.